Pengaruh Media Pendingin Terhadap Kekuatan Tarik Hasil Pengelasan SMAW Material Pipa Baja Karbon Schedule 40 - Suryanto, Hendri; Ikhsan, Muhammad Arif Nur (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2025)
Cooling media is one of the factors that affect the quality of welding results. One indicator of the quality of welding results is the tensile strength test. This test is carried out to ensure the maximum tensile strength or stress that can be sustained by the material and its ability to withstand certain mechanical loads. This study was conducted to determine the effect of several types of cooling media, namely free air, distilled water, and SAE 40 oil on the tensile strength of SCH 40 carbon steel pipe material after being welded with SMAW welding. The conclusion obtained from the test data regarding the effect of cooling media on SMAW welding of SCH 40 carbon steel pipe material shows that cooling media with SAE 40 oil has the highest tensile strength and strain values of 714.38 N/mm2 and 6.19%, while the lowest tensile strength value is produced in distilled water cooling media, namely 592.44 N/mm2 and 4.33%.